Des solidarités in extenso pour un asile in extremis. Dégradation des conditions matérielles d’accueil à Marseille - Béatrice Mésini (Université des Sciences et Technologies de Lille, 2021)
In France, the duty ‘to protect persons threatened in their country’ is based on an impartial examination of the asylum application, the right to remain on the territory and to dignified reception conditions for the duration of the examination. However, the testimonies collected by the Marseille Asylum Observatory show that there are "systemic failures" in the administrative and logistical processing, which violate the "human dignity" and "integrity" of persons. We will analyse the 60 stories collected from asylum seekers and accompanying persons in 2017-2018 in order to grasp the modalities of wandering and abandonment of people. As a counterpoint, we will update the solidarity initiated by various actors (employees, activists, volunteers, and citizens), which is exercised in extenso by linking the city with vital information concerning access to basic needs. Finally, we will choose five judgements from the administrative Court of appeal of Marseille and the Council of State, which confirm or invalidate the rejection of material reception conditions, while prioritising and proportioning the rights and duties of guests.